MICROPOLITICS AND SMALLER PEDAGOGY: CONCEPTUAL DEVELOPMENTS TO THINK ABOUT EDUCATION BY WAY OF EXPERIMENTATION - Daniela da Cruz Schneider (Travessias, 2014)
This article aims to point out reverberations of the concept of micropolitics, from Gilles Deleuze and Flix Guattari, to think an minor education. It is a conceptual search, which tackles philosophical conceptions offset for the educational territory. Outlining the differences between higher and lower education, between macro and micropolitical, this text seeks ways to exit the territory dissected a reproductivist trend instrumental education, seeking a power point education guided by microgestos and by experimentation.